Neuropathic Symptoms, Quality of Life, and Clinician Perception of Patient Care in Medical Oncology Outpatients with Colorectal, Breast, Lung, and Prostate Cancer - Jones, Desiree (J Cancer Surviv, 2014)
PURPOSE: We investigated how treatment-induced neuropathic symptoms are associated with patients’ quality of life (QOL) and clinician-reported difficulty in caring for patients. METHODS: Data were obtained from 3106 outpatients with colorectal, breast, lung, or prostate cancer on numbness/tingling (N/T), neuropathic pain, and QOL. Clinicians reported the degree of difficulty in caring for patients’ physical and psychological symptoms. RESULTS: For all patients, moderate to severe N/T was associated with poor QOL (OR = 1.82, 95% CI: 1.47–2.26, P < 0.001) but neuropathic pain was not (OR = 1.31, 95% CI: 0.94–1.83, P = 0.114). Moderate to severe N/T and neuropathic pain were associated with increased care difficulty (OR = 1.49, 95% CI: 1.27–1.74, P < 0.001 for N/T, and OR = 1.46, 95% CI: 1.15–1.84, P = 0.002 for neuropathic pain). The association of neuropathic pain with care difficulty was most significant in patients with CRC (OR = 2.32, 95% CI: 1.41–3.83, P = 0.001). Baseline neuropathic pain was associated with declining QOL in CRC patients (OR = 2.08, 95% CI: 2.21–3.58, P = 0.008). CONCLUSIONS: Clinicians may experience increased care difficulty for patients of all cancer types with moderate to severe N/T or neuropathic pain; care difficulty due to neuropathic pain may be higher for CRC patients. Nearly half the patients of all cancer types with moderate to severe N/T may expect poor short-term QOL; CRC- but not other- patients with baseline neuropathic pain are likely to experience declining QOL. IMPLICATIONS FOR CANCER SURVIVORS: About half of patients with moderate to severe N/T (any cancer type) may expect poor QOL in the short-term; CRC patients with baseline neuropathic pain in particular may experience declining QOL.